Electrochemical catalytic cyclization reactions using environmentally friendly methodologies - Duñach, E. (2013)
The electrochemical intramolecular cyclisation of bromoalkoxylated derivatives 1 was carried out using Ni(II) complexes as the catalysts in ethanol solutions by constant-current electrolysis in one-compartment cell in the absence of sacrificial anodes as an environmentally friendly system. The reduction of the substrates proceeds via one-electron cleavage of the carbon–bromine bond to form radical-type intermediates that undergo cyclisation to afford cyclic ethers in moderate to good yields.